Analisis Rasio Profitabilitas Dan Rasio Aktivitas Sebagai Dasar Penilaian Kinerja Keuangan PT Angkasa Pura I Periode 2018-2022 - Nabila Allaini Nurzahra; Tenri S.P.Dipoatmodjo; Nurman Nurman; Anwar Ramli (Student Scientific Creativity Journal, 2024)
his research aims to analyze the financial performance assessment of PT Angasa Pura I for 2018-2022 using profitability ratios and activity ratios. This research is descriptive research which is studied quantitatively. The variables in this research are Financial Performance, Profitability Ratios and Activity Ratios. The population in this research is all financial reports at PT Angkasa Pura I. The sample for this research is the financial position report, assets, sales and profit and loss report of PT Angkasa Pura I for 2018-2022. Based on the results of financial data analysis of PT. Angkasa Pura I, as measured by financial data analysis, namely profitability and activity ratios from the 2018-2022 financial reports, can be concluded that the financial performance of PT. Angkasa Pura I had good performance in 2018 to 2019 but experienced a decline in 2020 to 2021 respectively which was caused by certain factors, one of which was external factors, namely the presence of Covid-19. However, the company PT. Angkasa Pura I has tried to improve the company's performance as assessed by the level of profitability and activity ratios which show good value in 2022 even though the profit generated is still negative.